MANAGEMENT ISSUES OF FOOD INDUSTRY ENTERPRISES IN THE CONDITIONS OF THE DIGITAL ECONOMY (European Journal of Emerging Technology and Discoveries, 2024)
The article considers the digital economy as the main factor in the further development of the country's economic sectors, in particular the food industry. Methods for the effective use and establishment of elements of the digital economy in the organization of the activities of enterprises of the food industry have been studied.